Target Body Temperature in Very Low Birth Weight Infants: Clinical Consensus in Place of Scientific Evidence - Perez, Anna; van der Meer, Frauke; Singer, Dominique (Frontiers in Pediatrics, 2019)
Background: Although thermal care is part of the daily routine in Neonatal Intensive Care Units (NICUs), scientific evidence on what is the appropriate body temperature for very low birth weight infants (VLBWI) is largely lacking. Aim: To find out to what extent the standards of thermal care vary among high-level NICUs, especially with respect to the target body temperature in VLBWI. Methods: An online survey with 21 questions on thermal care in three categories of VLBWI was sent to 149 NICUs in Germany, Switzerland, and Austria. Results and discussion: Out of 112 (75%) returned questionnaires, 87 (58%) were included into analysis. A significant increase in incubator settings (air temperature / relative humidity) with decreasing gestational age and birth weight was reported, according to common textbook recommendations. However, a uniform target body temperature of 36.99  0.19 °C was chosen for all VLBWI categories. Likewise, the cut-off points for hypo- and hyperthermia were defined very similarly and showed low inter-center variability. This is a remarkable finding in view of the fact that the body temperature of mammalian fetuses in utero is 0.5-1.0 °C higher than that of the mother. Conclusion: Despite lacking scientific evidence, there is a tacit consensus among high-level NICUs that 37.0 °C is the appropriate body temperature in VLBWI, regardless of gestational age and birth weight. As this is below the intrauterine “breeding temperature” of the fetus, further research on this topic is warranted.